Impact of organizational culture on organisational performance: A study on the employees in educational institutions - Mesfin Korma; Naveen Kolloju; Harshavardhan Reddy Kummitha; Mohanad Ali Kareem (Business Systems Research (BSR), 2022)
Background: The purpose of the paper is to assess organisational culture's role on the performance of employees in the educational sector. Objectives: The paper seeks to address: what type of organisational culture is contributing to organisational performance, how organisational learning can be enhanced, how team orientation can be encouraged, and technical assistance and innovation can be promoted in developing economies. Methods/approaches: The data was collected from 350 respondents from different educational institutes' employees of the Garage zone of SNNPR, Ethiopia. Structural equation modelling was used to test the proposed hypothesis. Results: The results showed that organisational dimensions such as organisational learning, team orientation and strategic direction and intent are supported, and it is proved that these dimensions can significantly influence the overall performance of the organisation in the study area, whereas the remaining two dimensions: creating change, and goals and objectives are not supported by their organisations. Conclusions: The study concludes that the culture of creating change can enable organisations to achieve their goals and objectives. Organisations must focus on improving the capability of human resources. Especially, it is compulsory for the employees of the educational institutions as they must adopt technological assistance and other types of knowledge of value to encourage innovative practices in the teaching-learning process.
Keywords: L2; M21; O31; 330; Espoused values; Organizational Culture; Organisational Performance; Public Service Sector